Demand Analysis of Young Coconuts in Pasar Pedati Village, Central Bengkulu - Syafitri, Aida; Yumiati, Yossie; Yulihartika, Rika Dwi (PT. Sangadji Media Publishing, 2024)
Pasar Pedati Village in Central Bengkulu Regency is one of the regions with a relatively high production of young coconuts. The demand for young coconuts has been increasing yearly, driven by various factors, including population growth. This study aims to analyze the level of demand for young coconuts and assess the influence of factors such as the price of young coconuts, watermelon prices, traders' income, seasons, and sales systems on the demand for young coconuts in Pasar Pedati Village. This research employs a quantitative approach, utilizing questionnaires and interviews conducted with 65 young coconut traders selected using the census sampling technique. Data were analyzed using multiple coefficient of determination analysis (R²) with the assistance of SPSS Statistics 25 software. Hypotheses were tested using both simultaneous regression analysis (F-test) and partial regression analysis (T-test). The findings reveal that the demand for young coconuts is high, with 60% of respondents reporting strong demand. Partial analysis indicates that the price of young coconuts and traders' income significantly influence demand, while simultaneous testing shows that all independent variables collectively have a significant impact on the dependent variable. The adjusted R-square value is 0.856, indicating that 85.6% of the variance in young coconut demand is explained by the independent variables, namely, the price of young coconuts, watermelon prices, traders' income, seasons, and sales systems, while the remaining 14.4% is explained by other factors not included in this study.